Faktor-faktor Internal yang Mempengaruhi Mahasiswa Pendidikan Teknologi Agroindustri dalam Pemilihan Karir - Putri, Mega Kusumah; Handayani, Mustika Nuramalia (Program Studi Pendidikan Teknologi Agroindustri, UPI (Universitas Pendidikan Indonesia))
This study aims to determine 1) the influence of perceptions in career choice of agro-industrial technology education students; 2) the influence of motivational factors in career choice of agro- technology education students; 3) the influence of academic ability in career choice of agro- technology education students; 4) Which factor is most influential in career choice of agro-industrial technology education student. This research was descriptive with quantitative approach which examines the influence of relations independent and dependent variables. The study population is students of Agro-Industry Technology Education Study Program. These samples included 74 students of class 2012 and 2013. The data was collected by questionnaire and documentation of student GPA, data analysis using simple regression analysis and regression. The results showed that 1) the perception factors influence career choice of agro-industrial technology education students with contribution of 6.00%; 2) the motivational factors influence career choice of agro- industrial technology education students with contribution of 6.04%; 3) the academic abilities factors influence career choice of agro-technology career education students with 1.85% contribution; 4) The motivating factor is the most influential factor among the factor of perception and academic abilities factor in career choice of agro-industrial technology education students.Â